THE EFFECT OF HEDONIC SHOPPING VALUE AND BEAUTY INFLUENCER IN TIKTOK TOWARDS IMPULSE BUYING AMONG TIKTOK USERS IN MANADO - Kerin Tifany Saselah; S. L. H. V. Joyce Lapian; Emilia M. Gunawan (Universitas Sam Ratulangi, 2024)
Social media is becoming a tool for more intense, convenient, and innovative business-customer interactions, the phenomenon of impulse buying has become widespread. Tiktok as social media has a lot of impact on society including in terms of shopping. This study was conducted with the aim of determining the effect of hedonic shopping value and beauty influencers on impulse purchases. This type of research is descriptive quantitative, which is a study that aims to explain an empirical phenomenon accompanied by statistical data, characteristics and relationships between variables whose data collection techniques use questionnaires and literature studies. Data collection in this study was carried out through distributing questionnaires using a Likert scale. The sample in this study were people in Manado city totalling 116 respondents. The method used in data collection is purposive sampling. The analysis technique uses multiple linear regression analysis with the help of the SPSS 29 program. The results of this study indicate that the Hedonic Shopping Value variable has a positive and significant effect on the impulse buying variable and the beauty influencer variable also has a positive and significant effect on the impulse buying variable, both independent variables, namely hedonic shopping value and beauty influencers simultaneously affect impulse buying. Keyword: Hedonic Shopping Value, Beauty Influencer, Impulse Buying